2017
DOI: 10.3390/foods6120105
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter in Broiler Chicken and Broiler Meat in Sri Lanka: Influence of Semi-Automated vs. Wet Market Processing on Campylobacter Contamination of Broiler Neck Skin Samples

Abstract: Broiler meat can become contaminated with Campylobacter of intestinal origin during processing. The present study aimed to identify the prevalence of Campylobacter in broiler flocks and meat contamination at retail shops, and determine the influence of semi-automated and wet market processing on Campylobacter contamination of neck skin samples. Samples were collected from semi-automated plants (n = 102) and wet markets (n = 25). From each batch of broilers, pooled caecal samples and neck skin samples were test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
22
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 38 publications
6
22
1
Order By: Relevance
“…Our study revealed a significant prevalence of Campylobacter spp in poultry feces (67.96%) and in retail poultry carcasses (50%). These frequencies are consistent with those reported in previous studies conducted in Sri Lanka (Kottawatta et al, 2017) and in Ivory Coast (Goualié et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study revealed a significant prevalence of Campylobacter spp in poultry feces (67.96%) and in retail poultry carcasses (50%). These frequencies are consistent with those reported in previous studies conducted in Sri Lanka (Kottawatta et al, 2017) and in Ivory Coast (Goualié et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…Our study revealed a significant prevalence of Campylobacter spp in poultry feces (67.96%) and in retail poultry carcasses (50%). These frequencies are consistent with those reported in previous studies conducted in Sri Lanka (Kottawatta et al., ) and in Ivory Coast (Goualié et al., ). Conversely, a higher prevalence of Campylobacter was observed in poultry carcasses in Japan (Furukawa et al., ), in Maryland (Cui, Ge, Zheng, & Meng, ), and in poultry feces in the Netherlands (Schets et al., ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…N€ ather et al (2009) found that of 146 intensively reared flocks, 64 tested positive for Campylobacter spp, and, of the positive flocks, 66% were colonized by C. jejuni and 33% by C. coli. The association of campylobacters with poultry in developing countries is similar (Kottawatta et al 2017;Mageto et al 2018).…”
Section: Introductionmentioning
confidence: 95%
“…The situation in Sri Lanka is no different, and according to the Department of Animal Production and Health (DAPH) poultry meat and egg production now contributes to more than 70% of the livestock sector (DAPH, 2015). Previous studies conducted in Sri Lanka have found contamination of poultry with Salmonella, Campylobacter and E. coli (Kottawatta et al, 2017;Kamalika et al, 2008;Dissanayake et al, 2008), and Campylobacter has been identified as a common problem with about 64% prevalence at the farm level (Kalupahana et al, 2013). Another study conducted by Kottawatta et al (2014), covering 11 districts of Sri Lanka concluded that 9% of the samples from broiler flocks were positive for Salmonella.…”
Section: Introductionmentioning
confidence: 99%